Unusual chlorine partitioning in the 2015/16 Arctic winter lowermost stratosphere: observations and simulations - S. Johansson; M. L. Santee; J.-U. Grooß; M. Höpfner; M. Braun; F. Friedl-Vallon; F. Khosrawi; O. Kirner; E. Kretschmer; H. Oelhaf; J. Orphal; B.-M. Sinnhuber; et al. (Atmospheric Chemistry and Physics, 2019)
The Arctic winter 2015/16 was characterized by cold stratospheric temperatures. Here we present a comprehensive view of the temporal evolution of chlorine in the lowermost stratosphere over the course of the studied winter. We utilize two-dimensional vertical cross sections of ozone (O3) and chlorine nitrate (ClONO2), measured by the airborne limb imager GLORIA (Gimballed Limb Observer for Radiance Imaging of the Atmosphere) during the POLSTRACC/GW-LCYCLE II/GWEX/SALSA campaigns, to investigate the tropopause region in detail. Observations from three long-distance flights in January, February, and March 2016 are discussed. ClONO2 volume mixing ratios up to 1100 pptv were measured at 380 K potential temperature in mesoscale structures. Similar mesoscale structures are also visible in O3 measurements. Both trace gas measurements are applied to evaluate simulation results from the chemistry transport model CLaMS (Chemical Lagrangian Model of the Stratosphere) and the chemistry–climate model EMAC (ECHAM5/MESSy Atmospheric Chemistry). These comparisons show agreement within the expected performance of these models. Satellite measurements from Aura/MLS (Microwave Limb Sounder) and SCISAT/ACE-FTS (Atmospheric Chemistry Experiment – Fourier Transform Spectrometer) provide an overview over the whole winter and information about the stratospheric situation above the flight altitude. Time series of these satellite measurements reveal unusually low hydrochloric acid (HCl) and ClONO2 at 380 K from the beginning of January to the end of February 2016, while chlorine monoxide (ClO) is strongly enhanced. In March 2016, unusually rapid chlorine deactivation into HCl is observed instead of deactivation into ClONO2, the more typical pathway for deactivation in the Arctic. Chlorine deactivation observed in the satellite time series is well reproduced by CLaMS. Sensitivity simulations with CLaMS demonstrate the influence of low abundances of O3 and reactive nitrogen (NOy) due to ozone depletion and sedimentation of NOy-containing particles, respectively. On the basis of the different altitude and time ranges of these effects, we conclude that the substantial chlorine deactivation into HCl at 380 K arose as a result of very low ozone abundances together with low temperatures. Additionally, CLaMS estimates ozone depletion of at least 0.4 ppmv at 380 K and 1.75 ppmv at 490 K, which is comparable to other extremely cold Arctic winters. We have used CLaMS trajectories to analyze the history of enhanced ClONO2 measured by GLORIA. In February, most of the enhanced ClONO2 is traced back to chlorine deactivation that had occurred within the past few days prior to the GLORIA measurement. In March, after the final warming, air masses in which chlorine has previously been deactivated into ClONO2 have been transported in the remnants of the polar vortex towards the location of measurement for at least 11 d.